Modelling the current and future temperature suitability of the UK for the vector Hyalomma marginatum (Acari: Ixodidae) - Gillingham, Emma; Medlock, Jolyon M.; Macintyre, Helen; Phalkey, Revati (Ticks and tick-borne diseases, 2023)
Hyalomma marginatum is the main vector of Crimean-Congo haemorrhagic fever virus (CCHFV) and spotted fever rickettsiae in Europe. The distribution of H. marginatum is currently restricted to parts of southern Europe, northern Africa and Asia, and one of the drivers limiting distribution is climate, particularly temperature. As temperatures rise with climate change, parts of northern Europe currently considered too cold for H. marginatum to be able to survive may become suitable, including the United Kingdom (UK), presenting a potential public health concern. Here we use a series of modelling methodologies to understand whether mean air temperatures across the UK during 2000-2019 were sufficient for H. marginatum nymphs to moult into adult stages and be able to overwinter in the UK if they were introduced on migratory birds. We then used UK-specific climate projections (UKCP18) to determine whether predicted temperatures would be sufficient to allow survival in future. We found that spring temperatures in parts of the UK during 2000-2019 were warm enough for predicted moulting to occur, but in all years except 2006, temperatures during September to December were too cold for overwintering to occur. Our analysis of the projections data suggests that whilst temperatures in the UK during September to December will increase in future, they are likely to remain below the threshold required for H. marginatum populations to become established.